Spatial distribution characteristics and accessibility analysis in the Weibei Imperial Mausoleum Protection Zone under the hierarchical clustering algorithm - Xiaojie Feng (PLoS ONE, 2025)
This study mainly aims to investigate the spatial distribution characteristics and accessibility of the Weibei Imperial Mausoleum Protection Zone, and gain a deeper understanding of cultural heritage preservation and urban planning in this area. Settlements represent areas where people reside over the long term, including villages, towns, etc., and their spatial distribution reflects the interplay between human activities and the natural environment, as well as historical heritage. The relationship among population distribution, land use, cultural heritage preservation areas, and resident lifestyles can be understood by analyzing the spatial distribution of settlements. This is crucial for formulating effective urban planning and cultural heritage protection strategies. Initially, factor analysis is employed to reduce the dimensionality of the original multidimensional data. Subsequently, the hierarchical clustering algorithm is applied to categorize and cluster settlements based on these factors, then combines them into clusters, thereby revealing the spatial distribution patterns among different settlements. Next, this study constructs a settlement spatial distribution model based on factor analysis combined with the hierarchical clustering algorithm. Additionally, through accessibility analysis, this study examines the situation of residents accessing cultural heritage sites at different times during weekdays and weekends. The results indicate that with a classification number of 4, the Goodness of Variance Fit (GVF) for different hierarchical features exceeds 0.7, and the average silhouette coefficient reaches 0.58 at this classification number. Furthermore, the accessibility analysis also illustrates residents’ visiting patterns to cultural heritage sites on weekends and weekdays, providing valuable insights for urban planning and cultural heritage preservation. Therefore, this study concludes that categorizing settlements into four classes in this area is reasonable and emphasizes the importance of cultural heritage site preservation and urban planning. This method demonstrates a high level of accuracy and interpretability in spatial analysis.